Beyond hemodynamics: environmental and psychosocial predictors of anxiety in emergency patients with gastrointestinal bleeding - Kiyak, Ramazan; Taskin, Gokhan (Frontiers in Psychology, 2025)
PurposeWe investigated the state anxiety level and the factors affecting it in patients with Gastrointestinal Bleeding (GIB) who were followed up in the Emergency Department (ED).Material-methodsThe cross-sectional study was conducted with 107 patients (62 females, 45 males) who were admitted to the ED of Balikesir University Faculty of Medicine Hospital between 01.02.2025–10.05.2025 and diagnosed with GIB using the complete census method. In the study in which a correlational screening model was used, data were collected with the Demographic Information Form and the State Anxiety Inventory. Descriptive statistics, independent samples t-test, and One-way ANOVA tests were applied in the analysis.ResultsWhen the results of the study are examined, it is seen that the state anxiety levels of the patients followed up in the ED with the diagnosis of GIB are at a moderate level; there is no significant difference between state anxiety and gender, occupation, marital status and previous bleeding; and there are significant differences between state anxiety and being disturbed by the monitor machine sound in the environment of ED, being disturbed by the environment, being disturbed by the stretcher, being disturbed by the crowd, being disturbed by seeing other patients and being disturbed by not having physical communication with the outside. No statistically significant difference was found according to educational status.ConclusionsIt can be said that reducing the noise and chaos in the ED and providing a calmer and more supportive environment for the patient can reduce the state anxiety levels of patients with GIB and similar acute conditions and thus positively affect both their psychological wellbeing and medical outcomes. These findings may inform the development of targeted interventions—such as environmental modifications, structured patient education, or supportive practices—that can be implemented in the ED to enhance patient care.